PENERAPAN DIGITAL BEKASI BERANI BELI (BEBELI) PADA UMKM KABUPATEN BEKASI - Alviona Rahma Novita; Yunita Lasma; Nurlaila Maysaroh Chairunnisa (An-Nizam, 2023)
The Indonesian government has focused on procuring Small and Medium Enterprises (MSMEs) empowerment programs in society so that they are increasingly synergized with developments in the world of technology. For this reason, the Bekasi Government launched the Bekasi Berani Beli (BeBeLi) application as the first online store created by the Bekasi Government in order to encourage its people to use local products sold through the application. The regional government of Bekasi Regency has begun to slowly conduct socialization related to the procurement of the application, but it has not yet reached Karangharja Village. This is what encourages students participating in the Community Service Program (Devition of People) to assist the government in providing counseling or outreach to residents of Karangharja Village regarding the BeBeLi application. Devition of People activities will be carried out through two methods, namely the community education method and the training method. The community education method is carried out through outreach activities for the BeBeLi application, while training is carried out by providing training to Karangharja Village residents on how to use and register their products to the BeBeLi application. In this Devition of People activity this time the media used were print and broadcast media so the costs used were for the purposes of printing pamphlets and renting equipment used for socialization and distributing consumption to the villagers who attended. It is hoped that with this activity the Karangharja village residents can take advantage of the forums that have been created by the government and be able to realize local economic independence by encouraging the progress of MSMEs. This Community Service activity has an impact, namely helping to market local products to the Bebeli application in order to support the development of MSMEs in Bekasi Regency, especially Karangharja Village and the majority in Karangharja Village have used the Bekasi Berani Beli (Bebeli) Application after the training.